Company law directors: role and duties / Suwaibah Ismail - Ismail, Suwaibah (Faculty of Law, 1987)
A registered company i.e. a company incorporated by registration under the companies Acts, is regarded by the law as a person, just as a human being. This artificial or juristic person can own land and other property, enter into contracts, sue and be sued, have a bank account in its own name, owe money to others and be a creditor of other people and other companies, and employ people to work for it. The company's money and property belong to the company and not to the members or shareholders, although the members or shareholders may be said to won the company similarly, the company's debts are the debts of the company and the shareholders cannot be compelled to pay them, although if , for example, the company is being wound up and its assets do not realise a sum sufficient to pay its debts , a shareholder whose liability is limited by shares is liable to contribute to the assets up to the amount, if any unpaid on his shares . A Company, of course, can only act through human agents, and those who manage its business are called directors. But the directors are only agents of the company, with the powers of management given by the company's articles of association and usually with power to delegate any of their powers to managing director. The company is also liable for torts and crimes committed by its servants and agents within the scope of their employment or authority. This conception of a company as a corporation, i.e. a person separate and district from the other persons who are its members and directors, is the fundamental principle of company law.